Splitting method in multisite damage solids: mixed mode fracturing and fatigue problems - Cotta, Igor Frederico Stoianov (2016)
The design of complex structures demands the prediction of possible fracture-dominant failure processes, due to the existence of unavoidable preexistent flaws and other defects, as well as sharps and cracks. On one hand, the complexity of the structure and the presence of many defects to be accounted for in the modeling can become the computational effort impracticable. On the other hand, it is important to seek the development of a computational framework based on some numerical method to study these problems. A way to overcome the difficulties mentioned, therefore making feasible the analysis of complex structures with many cracks, flaws and other defects, consists of combining a representative mechanical modeling with an efficient numerical method. This is precisely the fundamental aim of this work. Firstly, the Splitting Method is used aiming to build a representative modeling. Secondly, the Generalized Finite Element Method (GFEM) is chosen as an efficient numerical method, in which enrichment strategies of the approximated solution using stress functions in particular can be explored. The GFEM framework also allows avoiding the excessive refinement of the mesh, which increases the computational effort in conventional finite element analysis. In the Splitting Method, a kind of decomposition method, the original problem is subdivided in local and global problems which are then combined by imposing null traction at the crack surfaces. In this work, the Splitting Method was completely programmed in Python language and its use extended to analyze crack propagation including fatigue crack growth. The generated code presents in addition to several features related to Fracture Mechanics concepts, as the computation of the stress intensity factor (mode I and II) trough J Integral. Some examples are presented to depict the propagation of the cracks in multisite damage structures. It is shown that for this kind of problems the enrichment strategy provided by GFEM is essential. Moreover, the final example demonstrates that the computational tool allows for investigation of different possible crack scenarios with a low cost analysis. One concludes about the representativeness and efficiency of the methodology hereby proposed.